Solving the small business paradox: E-commerce strategies for entrepreneurs - Anton W. Widjaja; Sugiarto Sugiarto; Dedi Kurniawan; Hong F. Sheng (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: Entrepreneurial orientation is an important construct in determining value-creation activities and firm growth. Developing digital capabilities should be a crucial part of an entrepreneurial process. Resource limitations have forced small- and medium-sized enterprises (SMEs) to do things reactively and responsively, without incorporating them as an integral part of their entrepreneurial process toward creating competitive advantages.